2017
DOI: 10.1016/j.colegn.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Older persons who re-present to the Emergency Department: An observational study

Abstract: Background: Models of emergent care evolve in response to an ageing population. The Medical Assessment Unit (MAU) receives patients from the Emergency Department (ED) for up to 48 hours to facilitate assessment, care and treatment before discharge home or to another inpatient unit. Aim: To describe the clinical and social characteristics of older people who had a stay in the MAU and then represent to the ED within 28 days of discharge from hospital. Methods: A retrospective observational study design was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This is routinely used to communicate to general practitioners (GPs), patients and their carers, about the reason for hospitalization, treatment provided, medications at the time of discharge, and arrangements for follow-up services after discharge (Kripalani et al, 2007). Some studies have reported that the availability of discharge summaries at the first post-discharge visit can be as low as 12-34% (Kripalani et al, 2007), and only 28% of older people representing to the emergency department had a discharge summary from the last admission (Grealish, Forbes, Beylacq, Adeleye, & Crilly, 2017). Furthermore, the information in discharge summaries is reported to be inadequate, and details about diagnostic test results, patient or family counselling, discharge medications, and follow-up plans have been reported to be missing in several studies (Cummings et al, 2010;Groene, Orrego, Suñol, Barach, & Groene, 2012;Kripalani et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is routinely used to communicate to general practitioners (GPs), patients and their carers, about the reason for hospitalization, treatment provided, medications at the time of discharge, and arrangements for follow-up services after discharge (Kripalani et al, 2007). Some studies have reported that the availability of discharge summaries at the first post-discharge visit can be as low as 12-34% (Kripalani et al, 2007), and only 28% of older people representing to the emergency department had a discharge summary from the last admission (Grealish, Forbes, Beylacq, Adeleye, & Crilly, 2017). Furthermore, the information in discharge summaries is reported to be inadequate, and details about diagnostic test results, patient or family counselling, discharge medications, and follow-up plans have been reported to be missing in several studies (Cummings et al, 2010;Groene, Orrego, Suñol, Barach, & Groene, 2012;Kripalani et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impact of discontinuity on service delivery can result in delayed recovery and readmission to hospital (Naylor & Keating, 2008); carers might feel unsupported and that it is necessary for them to take responsibility to compensate for inadequacies in the health system (Hvalvik & Reierson, 2015). Previous studies about discontinuity in transitional care have been focused on older people (Cheen et al, 2017;Grealish et al, 2017;Hvalvik & Reierson, 2015) and people with dementia (Kable et al, 2015) or diminished cognition (Groene et al, 2012), carers of stroke survivors (King et al, 2010;Luker et al, 2017;Pindus et al, 2018), and general hospital admissions (Ziaeian, Araujo, Van Ness, & Horwitz, 2012). These studies have been conducted in Australia, Singapore, Norway, the USA, and Spain (participating in the HANDOVER project) (Groene et al, 2012), and results might be relevant to other similar health-care systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The nurse navigator role was introduced in the cancer field in the early 21st century (Freeman & Rodriguez, 2011). The nurse navigator has become a widely recognised role in integrated healthcare systems, working with people living with chronic disease to help them understand their disease and care (McMurray & Cooper, 2017), which in turn is expected to improve the person's ability to self‐care and therefore avoid hospitalisation (Grealish, Forbes, Beylacq, Adeleye, & Crilly, 2017). The nurse navigator is a pivotal point of contact to identify and link the person to the health and social services across the tertiary and primary sectors (Douglas, Schmalkuche, Nizette, Yates, & Bonner, 2018; Spooner et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 95% of patients had a discharge summary but for 19% the summaries were not completed or transmitted to primary care givers within two weeks [22]. In one Australian study, discharge summaries were not available for 72% of the sample, especially for those aged 70 to 80 years, compared to those over 80 years old [23].…”
Section: Discussionmentioning
confidence: 99%